Die Verstädterung der Eigentumsverhältnisse bei Stadterneuerungsverfahren an ausgewählten Beispielen aus der Bundesrepublik Deutschland - Aust, Bruno (ERDKUNDE, 1980)
Several projects of urban renewal carried out in the first half of 1970s are studied with respect to the change of property rights. The extension of an inner city area in Hamburg-Altona, the renewal of the historical town centre of Kempten (Allgau) and a public housing project in Berlin Wedding are taken as examples. Far-reaching changes in property structure are the common feature of all these different case studies: the number of proprietors is drastically reduced, particularly the small private landowners are driven out,and much of the central area of the city gets into the hands of building companies, banks, and insurance companies. The urban renewal projects studied primarily aimed at changing the structure of urban land use, removing the worst deficiencies in living conditions, improving the visual outlook of the cities, etc. Both legislative and financial measures were used to carry out the urban renewal projects mentioned; which measure was taken was decided by their agreement, or disagreement, with the specific situation of the market. The public authorities very rarely made any use of their possibilities of influencing the property structure, even in official renewal areas.